The Histidine Kinase Domain of UhpB Inhibits UhpA Action at the Escherichia coli uhpT Promoter - Wright, Jesse S. (American Society for Microbiology, 2000)
The histidine kinase (HK) component of many two-component regulatory systems exhibits regulated ability to phosphorylate itself and to participate in transfer of phosphate to and from its cognate response regulator. The signaling system that controls expression of the UhpT sugar phosphate transporter in Escherichia coli in response to external glucose 6-phosphate includes the HK protein UhpB and the polytopic membrane protein UhpC, a UhpT homolog which is required for responsiveness to an inducer and activation of UhpB. The existence of a UhpBC signaling complex is suggested by the requirement for UhpC for the activity of certain constitutively active variants of UhpB, the dominance and epistasis relationships of uhp alleles, and the finding that expression of UhpB in excess of UhpC has a strong dominant-negative effect. Expression of a hybrid protein containing the cytoplasmic C-terminal half of UhpB fused to glutathione S-transferase (GST) also interfered with Uhp signaling. This interference phenotype could not result solely from the phosphatase activity of UhpB, because interference affected both overexpressed UhpA and UhpA variants which are active in the absence of phosphorylation. Variant forms of UhpB which were active in the absence of UhpC carried amino acid substitutions near motifs conserved in HK proteins. The GST fusion protein inhibited the ability of UhpA to bind and activate transcription at the uhpT promoter. Unlike the wild-type situation, a GST fusion variant carrying one of the UhpB-activating substitutions, R324C, displayed autokinase activity and phosphate transfer to UhpA but retained the ability to sequester UhpA when it was altered in the conserved residues important for phosphate transfer. Thus, the default state of UhpB is kinase off, and activation of its phosphate transfer activity requires either the action of UhpC or the occurrence of certain mutations in UhpB. The interference phenotype shown by UhpB in excess of UhpC appears to include the binding and sequestration of UhpA.